HOW TO CREATE SOCIAL COHESION DURING PANDEMIC? A SOCIOLOGICAL ANALYSIS OF DIGITAL VOLUNTARISM AS THE PATH OF THE RECONSTRUCTION OF RELIGIOUS CONSCIOUSNESS IN INDONESIA - Andri Azis Putra (Jurnal Sosiologi Reflektif, 2022)
The most important function of religious rituals is to accept the expression of shared values and goals in society. This function combines social awareness with patterns of interaction in creating solidarity. Currently, social distancing has been seen by many Indonesians as the cause of the degradation of the value of spiritual intimacy in religious rituals. Meanwhile, the need to accept the “New Normal” in all aspects of daily life is absolute for citizens. Therefore, a new conception of this claim is certainly needed to accommodate the pressure in the adaptation process to the "New Normality of Ritual". This study examines the efforts of digital volunteerism to reconstruct religious consciousness among religious people in Indonesia. The research was conducted with descriptive qualitative methods and using Sociology as an approach in the analysis. The results of this study indicate that digital volunteerism efforts can gradually reconstruct religious consciousness in the community, especially during the pandemic. Eventually, this reconstructed religious consciousness will be able to strengthen social cohesion that was previously reduced when social distancing policies were implemented during the pandemic.Fungsi terpenting dari ritual keagamaan adalah menerima ekspresi nilai dan tujuan bersama dalam masyarakat. Fungsi ini menggabungkan kesadaran sosial dengan pola interaksi dalam mendorong solidaritas. Saat ini, social distancing telah dilihat oleh banyak umat beragama di Indonesia sebagai penyebab degradasi nilai keintiman spiritual dalam ritual keagamaan. Sementara itu, kebutuhan untuk menerima “New Normal” dalam segala aspek kehidupan sehari-hari adalah mutlak bagi warga negara. Oleh karena itu, konsepsi baru atas klaim ini tentu diperlukan untuk mengakomodir tekanan dalam proses adaptasi terhadap "ritual kenormalan baru". Penelitian ini mengkaji upaya voluntarisme digital untuk merekonstruksi kesadaran beragama di kalangan umat beragama di Indonesia. Penelitian dilakukan dengan metode kualitatif deskriptif dan menggunakan Sosiologi sebagai pendekatan dalam analisis. Hasil penelitian ini menunjukkan bahwa upaya voluntarisme digital secara bertahap dapat merekonstruksi kesadaran keagamaan pada masyarakat khususnya di masa pandemi. Pada tahap selanjutnya, kesadaran keagamaan yang terekonstruksi ini dapat memperkuat kohesi sosial yang sebelumnya telah tereduksi ketika kebijakan social distancing diterapkan di masa pandemi.